Metodologia unificada para cálculo dos esforços eletromecânicos de barramentos flexíveis em subestações elétricas de transmissão - Lima Junior, Ilton de (2021)
Executive design is necessary to build an electrical transmission substation (SE). One component of such work is the electromechanical design. Among the various attributions of the electromechanical subject, the requirements for structures stand out. They consist of drawings, diagrams, and memorials used to calculate the efforts applied by rigid or flexible busbars on their supporting structures. Flexible busbars, whose efforts mentioned above, are classified as static or dynamic. They occur due to busbar traction and weight, wind incidence and short-circuit situations. Even though, the methods to determine each effort are mainly contained in technical standards, plus are also brought by other bibliographic references. However, this information lacks guidance on how to combine them in a full design. Besides, there is no computational tool, professionally available, that is useful to design companies. This work’s main objective is the development of a unified methodology, and its computational implementation, for the complete electromechanical design of flexible busbars efforts in Ses. The proposed methodology and the software’s implementation are detailed. Some design simulations are presented, based on typical busbar arrangements of Ses, as well as examples of sensitivity analyses of variables, using an implemented functionality that assists the engineer in decisions to optimize the efforts’ values. The unified methodology validation is performed through comparisons with results from examples contained in the technical standards and other selected references. Therefore, the present work has as main contribution the development of the unified methodology, with practical application through a software. The tool has commercial potential and has already been used professionally. In addition, this research helps to fill a gap identified in the current bibliography and cover several information regarding the design of flexible busbar efforts. This can also serve as a professional guide for engineers.